Ambition : why it's good to want more and how to get it - Bridge, Rachel (Capstone, 2016)
"Be bold. Be brave. Embrace your ambition. Ever have that nagging feeling that you are better than the sum of your current achievements? Do you have a secret desire to be achieving much more, to change the world or to reach the top of your game? Then it is time to use your ambition to your advantage. It has been proven that ambitious people achieve greater levels of success, whether that be a higher level of education, a more prestigious job, a higher income or more satisfaction in life. Grounded in scientific research and with contributions from people at the height of their success in business, music, the arts and sport, Ambition will help you to harness your aspirations to achieve your lifetime goals. It will give you practical insights into how to use your talents and learn from others who have done it before, so that you can get to where you want to be. If you want to get that promotion, achieve that big life-changing goal, start your own successful business, receive that distinctive acclaim, or make a positive difference to the world, then the good news is that you already have the fuel of ambition in you. This book will show you how to use it to drive your success. Reveals how you can do more than you think with what you've already got Helps discover your true motivation using a psychology model and shows you how to use that as the fuel for greater success Contains insights from successful people in all fields including John Torode, Myleene Klass, Will Greenwood, Katie Hopkins and Gavin Patterson Shows that the world is an exciting place and you can do anything if you use your ambition to help you "--